STRATEGIES TO ENHANCE EMPLOYEE ENGAGEMENT IN INNOVATION: A CASE STUDY OF TELKOM INDONESIA WILAYAH MEDAN - J. Arnold Parlindungan Gultom; Iskandarini; Vivi Gusrini Pohan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to analyze the internal and external factors affecting employee engagement in innovation at PT Telkom Indonesia Wilayah Medan and formulate strategies to enhance it. The research methodology employs The Strategy Formulation Analytical Framework, including the Input Stage, Matching Stage, and Decision Stage. Data was collected through questionnaires completed by 43 employees, through interviews, and focus group discussions. The analysis revealed 20 internal factors (9 strengths and 11 weaknesses) and 20 external factors (9 opportunities and 11 threats) influencing employee engagement in innovation. From these findings, 10 strategies were formulated, and through focus group discussions, 5 key strategies were prioritized for implementation: providing dedicated time and space for innovation activities during working hours, adjusting workloads and tasks to include innovative activities, enhancing personal responsibility and innovative solutions with access to the latest technology, strengthening cross-departmental collaboration, and promoting a proactive sharing and implementation culture of innovative ideas.